2014
DOI: 10.1016/j.neuron.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Slow and Fast Gamma Rhythms Coordinate Different Spatial Coding Modes in Hippocampal Place Cells

Abstract: SUMMARY Previous work has hinted that prospective and retrospective coding modes exist in hippocampus. Prospective coding is believed to reflect memory retrieval processes, whereas retrospective coding is thought to be important for memory encoding. Here, we show in rats that separate prospective and retrospective modes exist in hippocampal subfield CA1 and that slow and fast gamma rhythms differentially coordinate place cells during the two modes. Slow gamma power and phase-locking of spikes increased during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
219
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(250 citation statements)
references
References 60 publications
26
219
2
Order By: Relevance
“…In both of these studies, the response to the predicted stimulus entailed a lower and the response to the unpredicted stimulus a higher frequency band. Similarly, a recent study in rodent hippocampus compared track runs with retrospective and prospective coding (Bieri et al, 2014). During retrospective coding, place fields reflect recently visited locations and therefore likely memory encoding.…”
Section: Discussionmentioning
confidence: 99%
“…In both of these studies, the response to the predicted stimulus entailed a lower and the response to the unpredicted stimulus a higher frequency band. Similarly, a recent study in rodent hippocampus compared track runs with retrospective and prospective coding (Bieri et al, 2014). During retrospective coding, place fields reflect recently visited locations and therefore likely memory encoding.…”
Section: Discussionmentioning
confidence: 99%
“…This shift in sequence content around landmarks imposed a distinctive organization on the hippocampal representation of space, in which semi-discrete, landmark-bounded "chunks" of the environment emerged [ 18 ]. A recent study of rats performing a linear track task reported a similar result, with CA1 place cell activity appearing more forward-directed as subjects left feeder sites at the ends of the track and more backward-looking on approach to feeders [ 71 ]. Interestingly, forward representations were associated with greater LFP power in the low gamma frequency (25-55 Hz) range, suggesting coupling between CA1 and CA3.…”
Section: From Phase Precession To Theta Sequencesmentioning
confidence: 89%
“…A considerable body of work has shown that this spiking in the hippocampus and entorhinal cortex is time locked to local gamma-activity, such that firing is effectively limited to discrete, gamma-locked time windows (see [56] and [57]). Bieri, Bobbitt, and Colgin [58] similarly observed theta-gamma phase precession in rat CA1 hippocampal cells and suggested differential relationships between coupling between high-and low-gamma signals. Phase precession has likewise been observed in entorhinal grid cells [59], supporting the organization of multi-item WM by way of theta-and gamma-cycles as by Lisman and Idiart's [39] model and its elaborations.…”
Section: Empirical Support For the Theta-gamma Neural Codementioning
confidence: 81%
“…The Lisman and Idiart [39] model predicts different thetaphase preferences for different stimuli, represented by individual gamma cycles superimposed upon a theta cycle, in a memory sequence. The discussed phenomenon of phase-precession observed in rodents [50,51,56,58,59] represents one of the primary pieces of evidence supporting the theory and contributing to its continued consideration, and recent work has shown progressive shifts in gamma activity based on stimulus sequence [77]. However, paradigms that would allow for investigation of differential phase-preferences for individual stimuli in a spatial memory sequence are decidedly absent from human study.…”
Section: Conclusion: the Theta-gamma Neural Code And Visuospatial Wmmentioning
confidence: 99%